A case of late distant recurrence/metastasis (≧10 years after curative surgery) of anaplastic lymphoma kinase-rearranged lung cancer and the review of similar cases in the literature - Shohei Matsuo; Yoshitane Tsukamoto; Eiichiro Mabuchi; Shunichi Negoro; Seiichi Hirota (Elsevier, 2020)
We experienced a 70-year-old female with brain and liver tumors. She underwent surgical operations for rectal cancer 8 year ago and lung cancer 16 years ago. Surgical removal of a brain tumor and a liver biopsy were performed. The brain tumor consisted of an adenocarcinoma with a solid signet-ring cell pattern. Under the possibility of metastatic anaplastic lymphoma kinase (ALK)-rearranged lung cancer in the brain and liver, immunohistochemistries (IHCs) for ALK were performed, returning positive results. Thus, metastasis of ALK-rearranged lung adenocarcinoma in the brain and liver had been confirmed. The patient was administered alectinib, which was well tolerated and has been in partial response for about one year and a half. By the genetic analyses for EML4-ALK variants, both the previous lung cancer and metastatic brain tumor were shown to harbor the same EML4-ALK variant 3 fusion. We thus concluded that ALK-rearranged lung adenocarcinoma has recurred as liver and brain metastases 16 years after curative surgery.